The Future of Healthcare and Health Transformation in Saudi Arabia: Challenges and Opportunities - Ahmed, Yasir Awad; Zakri, Ibrahim Ahmed; Aldawsari, Barrak Mohammed; Alotaibi, Munahi Safar Munahi; Alshammri, Bandar Kammash; Alenazi, Muneera Rafea; Alruwaili, Ashwaq Murdhi; Alzamil, Mona Mohammed; Alshehri, Sultan Ali (Journal of Ecohumanism, 2024)
This paper assesses the challenges and opportunities arising from health transformation in the Kingdom of Saudi Arabia, particularly within the Saudi Vision 2030. Several challenges, coupled with few opportunities, pose threats to achieving the respective vision's stated health goals. Of particular importance are the challenges of providing global best value care and lower health literacy of the population. A significant opportunity lies in the option to leapfrog regional and global health demographics by leveraging technology and adopting value-based care. Another opportunity is through public medical education and professional citizen ownership of their own health. The paper suggests necessitating a health realization economy with health SMEs playing a pivotal role, working in true ecosystem collaboration. With the ecosystem approach, health transformation in the Kingdom ultimately emphasizes leverage over scale. (Chowdhury et al., 2021).